The role of platelet-rich plasma (PRP) in pediatric surgery and regenerative medicine - Konyk, T.; Trokhymenko, M. (Journal of Education, Health and Sport, 2025)
Background. Platelet-rich plasma (PRP) is an autologous plasma concentrate containing platelets, growth factors, and cytokines. It promotes tissue regeneration by accelerating healing, reducing inflammation, and enhancing recovery. The use of an autologous source minimizes the risks of immune rejection. PRP is particularly valuable in pediatric surgery, particularly for enhancing tissue regeneration after trauma, correcting congenital anomalies, and improving postoperative healing, offering advantages where traditional methods are less effective. The aim. To analyze and summarize data on the effectiveness of platelet-rich plasma (PRP) in tissue regeneration in pediatric surgery patients. The study focuses on the role of PRP in accelerating wound healing, stimulating bone regeneration, and reducing the risk of postoperative complications. The key objective is to evaluate the potential of PRP as an adjunct to standard surgical techniques, particularly bone grafts or reconstructions, for its integration into routine pediatric practice. Materials and methods. The research methodology consisted of a systematic review of scientific publications from the PubMed and ELSEVIER databases from 2000 to 2024. The selection criteria were English-language articles (clinical studies and reviews) that focused on the clinical application of PRP for tissue regeneration in pediatric surgery (patients under 18 years of age). The analysis focused on evaluating the efficacy and safety of PRP in the pediatric population. Results. PRP acts as a controlled delivery system for bioactive molecules, modulating inflammation, stimulating cell proliferation, angiogenesis, and extracellular matrix synthesis. Growth factors released from α-granules, such as PDGF, TGF-β, VEGF, and EGF, are the basis for regeneration. In a randomized study of infants with meningomyelocele, PRP gel applied to the defect site significantly reduced cerebrospinal fluid leakage (5% vs. 45%), meningitis (0% vs. 35%), partial skin necrosis (15% vs. 65%), and wound dehiscence (15% vs. 35%; all p < 0.05). In treating pilonidal sinus in adolescents, PRP gel reduced healing time, pain, and antibiotic use (p < 0.001). In Snodgrass urethroplasty (hypospadias), PRP reduced the incidence of urethrocutaneous fistulas (10% vs. 25%). In pediatric maxillofacial surgery (children aged 8-15 years), the combination of PRP with autogenous bone grafting after cyst enucleation showed significantly higher regeneration (94% defect filling after 6 months compared to 47% in the control group; p < 0.05). Conclusions. PRP is a safe, biocompatible adjuvant in pediatric surgery. It improves wound healing and bone regeneration outcomes and reduces complications in procedures such as treating hypospadias, pilonidal sinus, and meningomyelocele. The autologous nature of PRP eliminates the risks of immune rejection and infection. Adding PRP to bone grafts significantly enhances bone regeneration in children. Further research is needed to standardize preparation and dosage protocols, as variability affects outcomes.